PENGARUH FREE CASH FLOW, LIKUIDITAS, FINANCIAL LEVERAGE DAN OPERATING LEVERAGE TERHADAP KEPUTUSAN PEMBAYARAN DIVIDEN (Studi pada Perusahaan Manufaktur Subsektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2017) - Dwi Nugraha, Dimas Ardian (Jurnal Ilmiah Mahasiswa FEB, 2019)
Â ABSTRACTThis study aims to determine the effect of free cash flow, liquidity, financial leverage and operating leverage on the decision to pay dividends. The independent variable in this study is free cash flow, liquidity which is proxied using the current ratio, proxied financial leverage using debt to equity ratio and proxied operating leverage using depreciation. The dependent variable in this study is the decision to pay a dividend which is proxied by a dividend payout ratio. The population in this study were 18 food and beverage subsector companies listed on the Indonesia Stock Exchange in 2013-2017. Sampling using purposive sampling and obtained a sample of 7 companies. The analytical method used in this study is the multiple linear regression. The results of this study indicate that partially free cash flow has no significant effect on dividend payment decisions, liquidity has a positive and significant effect on dividend payment decisions, financial leverage does not have a significant effect on dividend payment decisions, and operating leverage has a negative and significant effect on dividend payment decisions.Keywords: Dividend Payment Decisions, Free Cash Flow, Liquidity, Financial Leverage, and Operating Leverage.